Effects of the flame retardant and lubricant types on fire retardancy effectiveness of medium density polyethylene - Samujło, B. (Polimery, 2022)
The effects (expressed as oxygen index values - OI) of selected commercial halogen free flame retardants (magnesium hydroxide and two grades of aluminum hydroxide) and three lubricants on the ignition and combustion resistances of the extruded medium density polyethylene (PE-MD) were investigated. The relations between the type and concentration of flame retardant (50-60 wt. %) or lubricant and oxygen index (OI- Fig. 1), heat of combustion (C(sp) - Fig. 2) related to Ol, and glow resistance (characterized with I(z) value - Table 1) were characterized. It was found magnesium hydroxide FR-20 (C) shows the best fire retardancy effectiveness then in turn less efficient were aluminum hydroxides: Martinal OL-107c (B) and JHK-M10 (A). The results obtained let place the materials investigated into the group of non-flammable and self-extinguishing ones.